Peningkatan Pengetahuan Pangan Sehat Aman Serta Kemampuan Pembuatan Bekal Sehat Anak Pada Orang Tua Murid TK Khalifah Jakarta 1: Improving the Knowledge of Safe Healthy Food and The Ability to Make Healthy Meals for Children in Parents of Students at TK Khalifah Jakarta 1 - Hikmawanti, Ni Putu Ermi; Fatmawati, Sofia; Wiyati, Tuti (LPPM STIKES Guna Bangsa Yogyakarta, 2024)
Children are an age group that experiences a period of rapid growth and development during this phase of life, so healthy and safe food intake is needed to support optimal growth and development. Therefore, education about healthy and safe food for parents (guardians) is expected to maintain children's health and build healthy lifestyles for them into adulthood. The aim of implementing this community service program (PPM) is to help increase the knowledge of parents (and guardians) in determining healthy and safe food for children and families. The target of delivering this PPM is to parents (and guardians) of students at TK Khalifah Jakarta 1, located around the Faculty of Pharmacy and Science Campus, UHAMKA, East Jakarta. Implementation of PPM is carried out through the socialization of healthy and safe food materials. Training on making and packaging healthy lunches is also carried out in this activity involving parents (and guardians). Evaluation of the success of this PPM activity is assessed using a questionnaire given before and after the implementation of the activity. Based on statistical analysis, the results showed that there was an increase in knowledge of healthy and safe food and the ability of parents (and guardians) of students to make healthy provisions for children by 72.2% (a=0.05).